A Combination Therapy of pHRE-Egr1-HSV-TK/Anti-CD133McAb-131I/MFH Mediated by FePt Nanoparticles for Liver Cancer Stem Cells. (12th June 2020) - Lin, Mei; Xiao, Yanhong; Jiang, Xingmao; Zhang, Jun; Guo, Ting; Shi, Yujuan
Abstract : It has been evidenced that liver cancer stem cells (LCSCs) are to blame hepatocellular carcinoma (HCC) occurrence, development, metastasis, and recurrence. Using iron-platinum nanoparticles (FePt-NPs) as a carrier and CD133 antigen as a target, a new strategy to targetly kill LCSCs by integrating HSV-TK suicide gene, 131 I nuclide irradiation, and magnetic fluid hyperthermia (MFH) together was designed and investigated in the present study. The results showed that FePt-NPs modified with PEI (PEI-FePt-NPs) could bind with DNA, and the best binding ratio was 1 : 40 (mass ratio). Moreover, DNA binding to PEI-FePt-NPs could refrain from Dnase1 enzyme digestion and could release under certain conditions. LCSCs (CD133 + Huh-7 cells) were transfected with pHRE-Egr1-HSV-TK by PEI-FePt-NPs, and the transfection efficiency was 53.65 ± 3.40 %. These data showed a good potential of PEI-FePt-NPs as a gene transfer carrier. 131 I was labeled with anti-CD133McAb in order to facilitate therapy targeting. The combined intervention of pHRE-Egr1-HSV-TK/anti-CD133McAb- 131 I/MFH mediated by PEI-FePt-NPs could greatly inhibit LCSCs' growth and induce cell apoptosis in vitro, significantly higher than any of the individual interventions (p < 0.05 ). This study offers a practicable idea for LCSC treatment, and PEI-FePt-NPs may act as novel nonviral gene vectors and a magnetic induction medium.